2011
DOI: 10.3945/ajcn.111.012377
|View full text |Cite
|
Sign up to set email alerts
|

N-nitroso compounds and cancer incidence: the European Prospective Investigation into Cancer and Nutrition (EPIC)–Norfolk Study

Abstract: Dietary NOC (NDMA) was associated with a higher gastrointestinal cancer incidence, specifically of rectal cancer. Plasma vitamin C may modify the relation between NDMA exposure and cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 31 publications
7
142
0
16
Order By: Relevance
“…Furthermore, fecal colon cells containing an O 6 -methylguanine DNA adduct, a characteristic promutagenic and toxic adduct formed by many NOCs, have been numbered and found to be significantly related to fecal excretion of ATNC in the stool of volunteers consuming meat in various diets (Lewin et al, 2006). In 2011, a large prospective study investigating the relation between dietary NOCs and the risk for cancer was performed (Loh et al, 2011). Exposure to endogenous NOCs was derived based on the estimated iron content from meat intake considering the relationship between the fecal ATNC and iron intake observed in several human controlled-diet studies (discussed above).…”
Section: Effect Of Heme On the Endogenous Production Of Nocmentioning
confidence: 99%
“…Furthermore, fecal colon cells containing an O 6 -methylguanine DNA adduct, a characteristic promutagenic and toxic adduct formed by many NOCs, have been numbered and found to be significantly related to fecal excretion of ATNC in the stool of volunteers consuming meat in various diets (Lewin et al, 2006). In 2011, a large prospective study investigating the relation between dietary NOCs and the risk for cancer was performed (Loh et al, 2011). Exposure to endogenous NOCs was derived based on the estimated iron content from meat intake considering the relationship between the fecal ATNC and iron intake observed in several human controlled-diet studies (discussed above).…”
Section: Effect Of Heme On the Endogenous Production Of Nocmentioning
confidence: 99%
“…Findings from the European Prospective Investigation into Cancer (EPIC), a large prospective study which investigated the association between dietary NOCs and cancer risk, showed that gastrointestinal cancer incidence and more specifically with risk of rectal cancer was associated with dietary NDMA (HR: 1.13; 95% CI: 1.00, 1.28; HR: 1.46; 95% CI: 1.16, 1.84 per 1-SD increase respectively) but not with endogenous NOCs or nitrite [10].…”
Section: Resultsmentioning
confidence: 99%
“…N-nitroso compounds (NOCs) can induce cancer in multiple organs in at least 40 different animal species, including higher primates [106][107][108]. In in vitro studies on human liver slices, the mechanism of action was shown to be nucleic acid alkylation [109].…”
Section: N-nitrosoglyphosate and N-nitrososarcosinementioning
confidence: 99%